Characteristics of glucomannan of Porang Flour (Amorphophallus oncophyllus) with Various Chemical Extraction Methods - Tety Desrita Handayani; Agustina Agustina; Eni Harmayani; Yudi Pranoto (Jurnal Sains dan Teknologi Pangan, 2023)
Porang plants are widely cultivated in Indonesia as a potential source of glucomannan. Glucomannan is obtained by separating impurity components such as starch, cellulose, protein, fat, and the rest of the flour bag from porang flour. The purpose of this study was to determine the effect of the isolation method on porang flour to produce high purity glucomannan. In this study, the extraction of glucomannan was carried out by a modified simple centrifugation method with the addition of aluminum sulfate (EAS), sodium metabisulfite (ENM), both (ENMAS), and no treatment (EK). All of the glucomannan obtained was then analyzed for composition, color, transparency, degree of acetylation and viscosity. The characteristics of porang glucomannan were then compared with konjac glucomannan (PKG). The results showed that ENMAS showed the highest value with a purity value of 93.71%, WHC 55.06 g water/g glucomannan, whiteness degree 79.16, and gel viscosity 73000 cps.